Clinician-Performed Bedside Ultrasound in Improving Diagnostic Accuracy in Patients Presenting to the ED with Acute Dyspnea - Papanagnou, Dimitrios (West J Emerg Med, 2017)
INTRODUCTION: Diagnosing acute dyspnea is a critical action performed by emergency physicians (EP). It has been shown that ultrasound (US) can be incorporated into the work-up of the dyspneic patient; but there is little data demonstrating its effect on decision-making. We sought to examine the impact of a bedside, clinician-performed cardiopulmonary US protocol on the clinical impression of EPs evaluating dyspneic patients, and to measure the change in physician confidence with the leading diagnosis before and after US. METHODS: We conducted a prospective observational study of EPs treating adult patients with undifferentiated dyspnea in an urban academic center, excluding those with a known cause of dyspnea after evaluation. Outcomes: 1) percentage of post-US diagnosis matching final diagnosis; 2) percentage of time US changed providers’ leading diagnosis; and 3) change in physicians’ confidence with the leading diagnosis before and after US. An US protocol was developed and standardized prior to the study. Providers (senior residents, fellows, attendings) were trained on US (didactics, hands on) prior to enrollment, and were supervised by an US faculty member. After patient evaluation, providers listed likely diagnoses, documenting their confidence level with their leading diagnosis (scale of 1–10). After US, providers revised their lists and their reported confidence level with their leading diagnosis. Proportions are reported as percentages with 95% confidence interval (CI) and continuous variables as medians with quartiles. We used the Wilcoxon signed-rank test and Cohen’s kappa statistics to analyze data. RESULTS: A total of 115 patients were enrolled (median age: 61 [51, 73], 59% female). The most common diagnosis before US was congestive heart failure (CHF) (41%, 95%CI, 32–50%), followed by chronic obstructive pulmonary disease (COPD) and asthma. CHF remained the most common diagnosis after US (46%, 95%CI, 38–55); COPD became less common (pre-US, 22%, 95%CI, 15–30%; post-US, 17%, 95%CI, 11–24%). Post-US clinical diagnosis matched the final diagnosis 63% of the time (95%CI, 53–70%), compared to 69% pre-US (95%CI, 60–76%). Fifty percent of providers changed their leading diagnosis after US (95%CI, 41–59%). Overall confidence of providers’ leading diagnosis increased after US (7 [6, 8]) vs. 9 [8, 9], p: 0.001). CONCLUSION: Bedside US did not improve the diagnostic accuracy in physicians treating patients presenting with acute undifferentiated dyspnea. US, however, did improve providers’ confidence with their leading diagnosis.